THE EFFECTS OF ENVIRONMENTAL CONDITIONS ON TAKEOFF DISTANCE AND CLIMB PERFORMANCE OF THE BOEING 737 MAX 8 - Septian Alvin Andrianto Andrianto; Lourenca Letizia pereira; Ferry Ardiansah Sulistyo; Hadi Prayitno (Politeknik Penerbangan Surabaya, 2025)
Takeoff and initial climb are critical phases of flight in which aircraft performance is strongly influenced by atmospheric, runway, and operational conditions. This study examines the effects of air temperature, atmospheric pressure, airport elevation, humidity, wind, runway condition, and aircraft weight on the takeoff distance and climb performance of the Boeing 737 MAX 8. The study employed a narrative literature-review method by analyzing peer-reviewed journal articles, aviation handbooks, and official technical publications related to aircraft performance. The findings indicate that high air temperature and high pressure altitude reduce air density, resulting in lower aerodynamic lift, reduced engine-performance margins, longer takeoff distances, and lower climb rates or climb gradients. Airport elevation intensifies these effects because atmospheric pressure generally decreases with increasing altitude. Headwinds normally improve takeoff performance by reducing the groundspeed required to achieve the necessary airspeed, while tailwinds produce the opposite effect. Humidity has a smaller influence than temperature and pressure but may contribute to reduced performance under hot-and-high conditions. Aircraft weight and runway condition further determine whether available runway length and obstacle-clearance requirements can be satisfied. The study concludes that these factors should not be assessed independently because their combined effects can create substantial operational limitations. Accurate weather observations, aircraft-specific performance calculations, appropriate runway selection, and careful aircraft-loading management are therefore essential for maintaining safe and efficient Boeing 737 MAX 8 operations.